Emergence of topological Mott insulators in proximity of quadratic band touching points - Mandal, I.; Gemsheim, S. (Condensed Matter Physics, 2019)
Recently, the field of strongly correlated electrons has begun an intense search for a correlation induced topological insulating phase. An example is the quadratic band touching point which arises in a checkerboard lattice
at half-filling, and in the presence of interactions gives rise to topological Mott insulators. In this work, we perform a mean-field theory computation to show that such a system shows instability to topological insulating
phases even away from half-filling (chemical potential µ = 0). The interaction parameters consist of on-site
repulsion (U), nearest-neighbour repulsion (V), and a next-nearest-neighbour correlated hopping (tc). The tc
interaction originates from strong Coulomb repulsion. By tuning the values of these parameters, we obtain a
desired topological phase that spans the area around (V = 0, µ = 0), extending to regions with (V > 0, µ = 0)
and (V > 0, µ > 0). This extends the realm of current experimental efforts to find these topological phases. Нещодавно, у галузi фiзики сильно скорельованих електронiв розпочались iнтенсивнi дослiдження кореляцiйно iндукованої топологiчної дiелектричної фази. Прикладом може слугувати точка дотику квадратичної зони, яка виникає на ґратцi типу шахiвницi при напiвзаповненнi, i в присутностi взаємодiй призводить до появи топологiчних мотiвських дiелектрикiв. В цiй роботi, ми здiйснили обчислення в наближеннi
середнього поля, щоб показати, що дана система демонструє нестiйкiсть по вiдношенню до топологiчних
дiелектричних фаз навiть далеко вiд напiвзаповнення (хiмiчний потенцiал µ = 0). Параметри взаємодiї
включають в себе одновузлове вiдштовхування (U), вiдштовхування мiж найближчими сусiдами (V) та
наступнi за найближчими сусiдами скорельованi стрибки (tc). Взаємодiя tc виникає завдяки сильному кулонiвському вiдштовхуванню. Регулюючи значення цих параметрiв, ми отримали бажану топологiчну
фазу, яка охоплює область в межах (V = 0, µ = 0), розповсюджуючись до областей з (V > 0, µ = 0) та
(V > 0, µ > 0). Це дає змогу розширити область поточних експериментальних зусиль з метою знаходження цих топологiчних фаз.